Investigating the potential of marine tourism climate change adaptation-mitigation strategies through environmental service market - Ramachandran, Sridar; Shuib, Ahmad; Mohammad Afandi, Syamsul Herman; Siow, May Ling (2012)
This is a conceptual paper that envision to ascertain marine resource position in addressing climate change impacts towards the tourism industry through environmental service market. It is imperative to mention that Asia comprising the largest proportion of global population illustrates lowest climate change adaptation concern. The lack of urgency is evident in the Malaysian scenario as it took almost a decade to establish a national climate change policy (2010) from the date the initial expression of interest (2000) was documented. However, this positive turn of event in the national government policy coupled with the vulnerability of the marine tourism industry to climate change has been the motivation to embark upon the study. Climate change in marine tourism being at an infancy stage especially in Malaysia is a primary research gap found in this study. Furthermore the emphasis on mitigation as opposed to adaptation strategies in government policies has become a deterring factor for tourism stakeholders to participate in the cause of climate change. Past studies have focused at one side of the market, namely the visitors; ignoring compensation requirements resulting in overestimation of project and economic benefits. Hence, this paper proposes a payment for environmental service (PES) approach bridging the gaps between the demand and supply sides of the market in addressing the marine tourism climate change adaptation-mitigation strategies. Consequently, this study envisage in charting a pathway for the marine tourism industry in combating tourism climate change vulnerability by striking a balance between the adaptation-mitigation strategies.